2009
DOI: 10.1002/anie.200901071
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Polymeric Dual Sensor for Temperature and pH Value

Abstract: The interest in "smart" functional materials that respond to changes in the environment strongly increased in the last years owing to the desire to control complexity and to create systems that adapt or respond to the environment. Moreover, such "smart" materials are used to design and develop new responsive materials for a wide range of applications in various fields, such as biotechnology, [1][2][3] drug delivery, [4][5][6] particle transport, [7] and optical sensing. [8][9][10][11] Recently, a thermorespons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
126
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 152 publications
(129 citation statements)
references
References 40 publications
1
126
2
Order By: Relevance
“…It has been reported that the extent of branching is higher 289 [186,187,229,577] 290 [175,203,305] 291 [211] 295 [308] 301 [165] 306 CSSQMA [389] 302 [164] 303 [209] 304 [305] 307 [578,579] 308 [579] 305 [212] 297 [188] 298 [201] 299 [201] 300 [387] 292 [189] 293 [173] 294 [210] Glycerol monomethacrylate Solketal methacrylate 296 [197,390] for conventional radical polymerization than for RDRP (ATRP, RAFT, and NMP). [443] A qualitative explanation was proposed in terms of the differences in the concentrations of short-chain radicals between RDRP and conventional radical polymerization.…”
Section: Acrylatesmentioning
confidence: 99%
“…It has been reported that the extent of branching is higher 289 [186,187,229,577] 290 [175,203,305] 291 [211] 295 [308] 301 [165] 306 CSSQMA [389] 302 [164] 303 [209] 304 [305] 307 [578,579] 308 [579] 305 [212] 297 [188] 298 [201] 299 [201] 300 [387] 292 [189] 293 [173] 294 [210] Glycerol monomethacrylate Solketal methacrylate 296 [197,390] for conventional radical polymerization than for RDRP (ATRP, RAFT, and NMP). [443] A qualitative explanation was proposed in terms of the differences in the concentrations of short-chain radicals between RDRP and conventional radical polymerization.…”
Section: Acrylatesmentioning
confidence: 99%
“…The response of the "smart" material to the external triggering event can be manifold too, ranging from surface energy switching [10,19], a shape change [20], variation in absorption or emission [12], or the material can undergo a phase transition [15,18]. "Smart" polymeric materials that undergo a phase-transition in water are in particular interesting for the development of responsive solutions, e.g., for the development of diagnostic tools and sensors [21][22][23]. The majority of such temperature induced solubility transitions are based on the lower critical solution temperature (LCST) behavior of polymers in aqueous solution, i.e., the polymer is dissolved at low temperature by favorable hydration while increasing the temperature leads to an entropy driven dehydration resulting in a collapse of the hydrophobic polymer chains [18,21,23].…”
Section: Introductionmentioning
confidence: 99%
“…"Smart" polymeric materials that undergo a phase-transition in water are in particular interesting for the development of responsive solutions, e.g., for the development of diagnostic tools and sensors [21][22][23]. The majority of such temperature induced solubility transitions are based on the lower critical solution temperature (LCST) behavior of polymers in aqueous solution, i.e., the polymer is dissolved at low temperature by favorable hydration while increasing the temperature leads to an entropy driven dehydration resulting in a collapse of the hydrophobic polymer chains [18,21,23]. Polymers exhibiting the opposite upper critical solution temperature (UCST) behavior in aqueous solutions, i.e., insoluble at low temperatures and soluble at elevated temperatures, are much less common [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The multi-optical response of the system to temperature, pH, oxygen content and saline conditions may constitute a drawback since the temperature response may be hindered by the change in other parameters but it is also an opportunity to design multiresponsive logic devices. 156,157 Polymer-based thermometers have the advantage of having higher sensitivities if only a narrow range (typically around room temperature) is requested. Also, these polymers can be designed as biocompatible beads, which is of fundamental importance for in vivo applications.…”
mentioning
confidence: 99%